2008
DOI: 10.1007/s00221-008-1338-4
|View full text |Cite
|
Sign up to set email alerts
|

ERP correlates of anticipatory attention: spatial and non-spatial specificity and relation to subsequent selective attention

Abstract: Brain-based models of visual attention hypothesize that attention-related benefits afforded to imperative stimuli occur via enhancement of neural activity associated with relevant spatial and non-spatial features. When relevant information is available in advance of a stimulus, anticipatory deployment processes are likely to facilitate allocation of attention to stimulus properties prior to its arrival. The current study recorded EEG from humans during a centrally-cued covert attention task. Cues indicated rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 73 publications
0
36
2
Order By: Relevance
“…We defined the time periods analogous to defining “components”, through an assessment of the range of post-cue latencies reported in the literature for the following four attention-related scalp components (Harter et al, 1989; Hopf & Mangun, 2000; Nobre et al, 2000a; van Velzen et al, 2002; Praamstra et al, 2005; Slagter et al, 2005; Simpson et al, 2006; Jongen et al, 2006; Green & McDonald, 2006, 2010; van der Lubbe et al, 2006; Grent-‘t-Jong & Woldorff, 2007; Dale et al, 2008). (1) An early, short duration process (Positivity contralateral early – Pce) occurring during 125–175 ms; (2) a subsequent component often referred to as the early directing attention negativity (EDAN) occurring between 250–350 ms; (3) a middle period associated with activity commonly called the anterior directing attention negativity (ADAN) occurring between 400–500 ms; (4) a late period toward the end of the cue delay up to the onset of the target, which would correspond to 800–1000 ms in this study, often called the late attention directing positivity (LDAP).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We defined the time periods analogous to defining “components”, through an assessment of the range of post-cue latencies reported in the literature for the following four attention-related scalp components (Harter et al, 1989; Hopf & Mangun, 2000; Nobre et al, 2000a; van Velzen et al, 2002; Praamstra et al, 2005; Slagter et al, 2005; Simpson et al, 2006; Jongen et al, 2006; Green & McDonald, 2006, 2010; van der Lubbe et al, 2006; Grent-‘t-Jong & Woldorff, 2007; Dale et al, 2008). (1) An early, short duration process (Positivity contralateral early – Pce) occurring during 125–175 ms; (2) a subsequent component often referred to as the early directing attention negativity (EDAN) occurring between 250–350 ms; (3) a middle period associated with activity commonly called the anterior directing attention negativity (ADAN) occurring between 400–500 ms; (4) a late period toward the end of the cue delay up to the onset of the target, which would correspond to 800–1000 ms in this study, often called the late attention directing positivity (LDAP).…”
Section: Methodsmentioning
confidence: 99%
“…Functional MRI studies have shown that multiple frontal, parietal and visual sensory regions are active during anticipatory deployment of visual spatial attention (Kastner and Ungerlieder, 2000; Corbetta and Shulman 2002; Serences and Yantis, 2006). Scalp ERP studies indicate that multiple direction-specific attentional stages occur within fractions of a second following a cue to covertly deploy attention to a spatial location in anticipation of a stimulus, and they support the possibility of different configurations of active cortical regions in each deployment stage, although the brain regions involved in each ERP stage are not well established (Nobre et al, 2000a; Hopf and Mangun 2000; Praamstra et al, 2005; Slagter et al, 2005; van der Lubbe et al, 2006; Dale et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Data from functional imaging (Coull and Nobre 1998;Gitelman et al 1999), electrophysiology (e.g. Foxe et al 1998Foxe et al , 2003Foxe et al , 2005aFoxe and Simpson 2005;Dale et al 2008) and of course, from hemi-spatial neglect patients (e.g. Heilman and van den Abell 1980;Perani 1986, 1987) have clearly implicated dorsal stream visual areas in the control of spatial attention mechanisms.…”
Section: Implications Of a Parvocellular Origin Of The ''C1'' For Attmentioning
confidence: 97%
“…Neuroimaging studies have also shown that posterior parietal regions are associated with the spatial mapping of auditory (Cohen, Russ, & Gifford, 2005;Weeks et al, 1999) and visual stimuli (Colby & Goldberg, 1999;Heinze et al, 1994). ERP studies of spatial attention reported evidence of bimodal spatio-temporal components during spatial attention tasks (Dale, Simpson, Foxe, Luks, & Worden, 2008;Green et al, 2005;Eimer, van Velzen, & Driver, 2002;Hopf & Mangun, 2000).…”
Section: Introductionmentioning
confidence: 99%